PENGARUH BIAYA PENGENDALIAN KUALITAS PRODUK TERHADAP PRODUK CACAT AIR MINUM DALAM KEMASAN KABUPATEN LEBAK - Abdul Hakim; Moch. Badru (Universitas La Tansa Mashiro, 2019)
Business competition in the bottled water beverage industry is getting tougher so that companies are able to reduce failures in running their businesses. One of them is controlling the number of defective products. Therefore, the company must have a product quality control system and for that reason it is necessary to allocate adequate costs so as to reduce the occurrence of defective products in its business activities. This study aims to determine the effect of product quality control costs on bottled water defect products at PT Etika Jayadi Makmur Lebak Regency.The research was conducted using descriptive quantitative methods. The study population is the entire production data which includes the number of defective products and quality control costs at PT. Jayadi Makmur Ethics. The research sample is data on the number of defective products and quality control costs at PT Etika Jayadi Makmur Lebak Regency in 2016-2018. Data analysis uses simple linear regression techniques.The results showed that: (1) the average cost of quality control per month that must be spent by the company is Rp. 3,025,555.60 and still below 3-5% of production costs; (2) the average percentage of defective products is still relatively high, namely above 1.5%, ideally not more than 1.5%; and (3) there is an influence of product quality control costs on defective products at PT. Jayadi Makmur Ethics of Lebak Regency which is shown by the t-value of 6.692 with a p-value of 0.044 which is smaller than 0.05.The study concluded that there is an effect of product quality control costs on bottled drinking water defects in PT Etika Jayadi Makmur, Lebak Regency. Furthermore, it is recommended that more extensive and complete research be carried out by adding the variables studied and the number of companies as comparative material.